1991
DOI: 10.1021/bi00243a002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of mitogenic factors from cementum

Abstract: Cementum is the mineralized structure through which soft connective tissues are attached to the teeth. It is a unique calcified tissue characterized by a low metabolic turnover, lack of blood supply, and presence of very few cells. However, it contains substances that influence the biological activities of fibroblasts of adjacent soft tissues. We have partially characterized cementum proteins that have mitogenic activity toward fibroblasts. Cementum was harvested from bovine teeth, and mitogenic factors were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…To facilitate connective tissue formation and attachment, attempts have been made to supplement planed roots with molecules such as fibronectin and growth factors; however, these substances have met with only a limited and variable degree of success (Caffesse et al, 1988;Nyman et al, 1988;Wikesjo et al, 1988;Lynch et al, 1989). The cementum proteins are likely to be a more logical choice for this purpose, because they are normal constituents of roots, and they promote a range of biological activities that are essential for periodontal regeneration (Miki et al, 1987;Nakae et al, 1989;Nishimura et al, 1989;Somerman et al, 1987Somerman et al, , 1989McAllister et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate connective tissue formation and attachment, attempts have been made to supplement planed roots with molecules such as fibronectin and growth factors; however, these substances have met with only a limited and variable degree of success (Caffesse et al, 1988;Nyman et al, 1988;Wikesjo et al, 1988;Lynch et al, 1989). The cementum proteins are likely to be a more logical choice for this purpose, because they are normal constituents of roots, and they promote a range of biological activities that are essential for periodontal regeneration (Miki et al, 1987;Nakae et al, 1989;Nishimura et al, 1989;Somerman et al, 1987Somerman et al, , 1989McAllister et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of cementum‐specific proteins remains questionable, although some putative cementum‐specific proteins have been invoked: a 55‐kDa CAP (263); a mitogenic factor (167); and a 72‐kDa protein, CEM‐1 (235). However, as the characterization and the sole expression by cementoblasts of these proteins have not been determined, the possible existence of cementum‐specific proteins remains unknown.…”
Section: Development Of the Periodontiummentioning
confidence: 99%
“…A precise characterization of the mineralized matrix as cementum is difficult, because the presence of cementumspecific proteins remains questionable. Although some putative cementum-specific proteins have been invoked such as the 56-kDa CAP (McAllister et al, 1990;Pitaru et al, 1995;Wu et al, 1996), a mitogenic factor (Nakae et al, 1991) and a 72-kDa protein (CEM-1, Slavkin et al, 1988), characterization of these proteins has been sparse and no particular cell type has been associated with their expression. In the present study, we showed that HERS cells synthesize a secreted as well as membrane-bound protein cross-reactive with a polyclonal antibody against CAP, thus supporting the idea that HERS cells are capable of producing cementum.…”
Section: Hers Produce a Cementumlike Mineralized Extracellular Matrixmentioning
confidence: 99%